IMPLEMENTATION OF SUBPROGRAMS OF THE FEDERAL SCIENTIFIC AND TECHNICAL PROGRAM FOR THE 2030 DEVELOPMENT OF AGRICULTURAL ECONOMY IN RUSSIA - Ivan SANDU; Vasily NECHAEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Increasing the efficiency of agricultural production and the need to ensure the technological sovereignty of the country in the current geopolitical conditions is of particular relevance. The purpose of the work is to study the impact of the implementation of subprograms of the Federal Scientific and Technical Program for the Development of Agriculture for 2017–2030 on technological changes in agricultural production of individual subsectors. As a result of the analysis of the effectiveness of the implementation of the subprograms of the Federal Scientific and Technical Progress of Russia for 2018-2022, trends in significant positive scientific and technological achievements in the production of sugar beets, potatoes, beef cattle breeding and feed production were identified. expansion of the domestic research base in the field of genetics, biotechnology, selection and breeding. Promising directions for the development of agricultural sectors for the long term have been developed, taking into account the implementation of the FNTP for the development of Russian agriculture. Various business models have been substantiated and mechanisms for stimulating the introduction of technologies have been created, taking into account the specific features of innovation processes in various industries.